2014
DOI: 10.1186/2193-1801-3-682
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the associations of osteoprotegerin gene with production traits in a paternal broiler line

Abstract: Improvements on growth and carcass traits in the poultry industry have been achieved by intense selection for heavier chickens at early ages. This faster growth has caused serious problems due to insufficient skeletal structure development needed to support the musculature of modern broilers. The osteoprotegerin gene (OPG), located on GGA2, is an important regulator of bone metabolism and reabsorption, being suggestive as a possible functional candidate gene associated with bone integrity in chickens. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…Park et al (2006) identified a QTL region associated with abdominal fat in broilers, where the TNFSF11 gene is mapped. Moreover, Fornari et al (2014) found significant (P < 0.05) associations between the osteoprotegerin gene (TNFRSF11B) and AFW and AFY traits in the same population used in this study. The TNFRSF11B gene acts as a decoy receptor of the TNFSF11 gene (Boyle et al, 2003).…”
Section: Genetic Association Analysismentioning
confidence: 82%
See 3 more Smart Citations
“…Park et al (2006) identified a QTL region associated with abdominal fat in broilers, where the TNFSF11 gene is mapped. Moreover, Fornari et al (2014) found significant (P < 0.05) associations between the osteoprotegerin gene (TNFRSF11B) and AFW and AFY traits in the same population used in this study. The TNFRSF11B gene acts as a decoy receptor of the TNFSF11 gene (Boyle et al, 2003).…”
Section: Genetic Association Analysismentioning
confidence: 82%
“…Further studies are required to elucidate the possible causes of the associations found in this study since the direct effect of the mutations, interactions with other genes, and/or the linkage disequilibrium between the SNPs and causative mutations resulting from an indirect effect (Fornari et al, 2014) may be responsible for the associations of the two SNPs studied here with several traits in this broiler population.…”
Section: Genetic Association Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic polymorphisms in the exon region of the GJA1 gene have been positively associated with various diseases in human (Kogame et al, 2014;Jamsheer et al, 2014), mice (Flenniken et al, 2005), and fish (Iovine et al, 2005). No available data associate the chicken GJA1 gene with growth traits, though several studies have been performed on other genes (Sato et al, 2012;Fornari et al, 2014) in chicken and have shown positive correlations with growth traits. Therefore, our discovery of a synonymous mutation in the chicken GJA1 gene and its significant association with growth traits suggests that this polymorphism could be used as a molecular marker for growth or muscle development traits in chicken.…”
Section: Discussionmentioning
confidence: 99%